(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: This study aims to analyze the budget impact of treatment costs for patients at Lê Văn Thịnh Hospital (LVTH) during the period from 2018 to 2023. Materials and methods: A cross-sectional descriptive study was conducted through a retrospective analysis of all direct medical costs (DMC) for patients with health insurance at LVTH during the period from 2018 to 2023. Data were extracted from the hospital’s management software, aggregated, processed, and analyzed using Excel and R. Results: During the period from 2018 to 2023, the total cost of medical treatment used for treating patients with health insurance was VND 1.075,107 billion, of which the health insurance fund covered 85.2%. Outpatient treatment costs accounted for 66.8% of the total, and drug costs constituted 57.8% of the overall expenditure. The study observed differences in the proportion of medical service costs between inpatient and outpatient treatments. Drug costs consistently represented the highest proportion, with the outpatient drug cost ratio being double that of inpatient treatment (73.7% vs. 30.5%). Analyzing DMC over three periods (2018-2019, 2020-2021, 2022-2023), the study found that the total DMC for both inpatient and outpatient treatments increased over time. For outpatient treatments, the proportion of drug costs increased progres- sively (68.7%, 73.6%, 74.9%). In contrast, for inpatient treatments, the cost proportions for surgery, diagnostic imaging, and hospital beds decreased over time, while the proportion of medical supplies costs increased. Conclusion: The analysis provides essential insights into the financial impact of treating patients with health insurance at LVTH over an extended period since the hospital adopted financial autonomy. These findings support the evaluation of LVTH’s financial resource utilization for professional activities during 2018-2023 and offer a basis for optimizing financial resources to enhance patient care services at LVTH.